PERAN KEPEMIMPINAN DALAM MENINGKATKAN KUALITAS PELAYANAN ADMINISTRATIF PADA UNIVERSITAS AL WASHLIYAH DARUSSALAM BANDA ACEH - Saddam; Jasmadi; Adnis AS; Yusra Jamali (Institut Ummul Quro Al-Islami Bogor, 2024)
The quality of administrative services at Al Washliyah Darussalam University Banda Aceh is a problem that needs to be addressed. This study aims to analyze the role of leadership in improving the quality of administrative services. The research method used is a qualitative approach with purposive sampling techniques, where data is collected through interviews and observations. The results of the study indicate that effective leadership contributes significantly to improving the quality of service, with an indicator of increasing student satisfaction. Where good communication and participatory decision-making by leaders play an important role in creating a productive work environment at Al Washliyah Darussalam University Banda Aceh. The study provides an overview that strengthening leadership in the university environment can improve the quality of administrative services. Recommendations for further research are to explore other factors that can affect the quality of service.